The Risk of Damage to Reailway Infrastructure Due to Theft and Devastation - Janowiec, Filip; Kula, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Theft and devastation of railway infrastructure are one of the most important factors that affect the safety of the railway transport system. In Poland, the railway transported 245.1 million passengers and 243.6 million tons of cargo in 2021, so it is extremely important to ensure the maximum possible safety standards. Theft and devastation of railway infrastructure contribute to significant material damage to railway network managers.
Keywords: railways; transportation; railway infrastructure; risk assessment; theft and devastation